NEDD4-2 and the CLC-2 channel regulate neuronal excitability in the pathogenesis of mesial temporal lobe epilepsy - Liu, Yuting; Yang, Haiyan; Zeng, Rongrong; He, Lu; Xiao, Ting; Peng, Xiaomei; Kuang, Zhuo; Wu, Liwen (Scientific reports, 2024)
An increasing number of studies have focused on the role of NEDD4-2 in regulating neuronal excitability and the mechanism of epilepsy. However, the exact mechanism has not yet been elucidated. Here, we explored the roles of NEDD4-2 and the CLC-2 channel in regulating neuronal excitability and mesial temporal lobe epilepsy (MTLE) pathogenesis. First, chronic MTLE models were induced by lithium-pilocarpine in developmental rats. Coimmunoprecipitation analysis revealed that the interaction between CLC-2 and NEDD4-2 . Western blot analyses indicated that NEDD4-2 expression was downregulated, while phosphorylated (P-) NEDD4-2 and CLC-2 expression was upregulated in adult MTLE rats. Then, the primary hippocampal neuronal cells were isolated and cultured, and the NEDD4-2 was knocked down by shRNA vector, resulting in decreased protein levels of CLC-2. While CLC-2 absence caused increased NEDD4-2 in cells. Next, in an epileptic cell model induced by a Mg 2+ -free culture, whole-cell current-clamp recording demonstrated that NEDD4-2 deficiency inhibited the spontaneous action potentials of cells, and CLC-2 absence caused more significant decrease in the spontaneous action potentials of cells. In conclusion, we herein revealed that NEDD4-2 regulates the expression of CLC-2, which is involved in neuronal excitability, and participates in the pathogenesis of MTLE.